Efforts to Increasing Numeracy Literacy of Elementary School Students Through Quiziz Learning Media - S Saefurohman; Rina Maryanti; Nissa Nur Azizah; Dwi Fitria Al Husaeni; Verra Wulandary; Asep Rudi Irawan (Universitas Pendidikan Indonesia (UPI), 2023)
A Study conducted by PISA in 2018 showed that Indonesian students’ mathematical abilities were at a low level of performance. It means that numeracy literacy of Indonesian students is very low. The purpose of this study was to predict how the effect of learning using the Quiziz application on students’ numeracy literacy in elementary schools. The method was used the single subject method by doing pretes and post-test. The results of study show that average post-test score of students is greater than the average pretest score. This is because the Quiziz application which is used as a learning medium can be made attractively using the various features provided so that students are more interested in learning. The study conclude that the Quiziz application can improve students’ numeracy literacy skills in elementary schools. The increase in literacy has an impact on the mindset of children in solving problems in every day life.